Imitation Of Human Arm And Hand Natural Movement For Telecommunication Application - Ramliy, Mohd Nazri (2003)
Gesture is an often overlooked, powerful tool used in our daily communication. In this research the imitation of human arm gesture is attempted for incorporating its application to telecommunication. A unilateral system to achieve this is implemented using robotic arm as the actuator for reconstructing arm gestures, and computer vision for the sensor.